2006
DOI: 10.1042/bj20060026
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for allosteric regulation of pH-sensitive System A (SNAT2) and System N (SNAT5) amino acid transporter activity involving a conserved histidine residue

Abstract: System A and N amino acid transporters are key effectors of movement of amino acids across the plasma membrane of mammalian cells. These Na+-dependent transporters of the SLC38 gene family are highly sensitive to changes in pH within the physiological range, with transport markedly depressed at pH 7.0. We have investigated the possible role of histidine residues in the transporter proteins in determining this pH-sensitivity. The histidine-modifying agent DEPC (diethyl pyrocarbonate) markedly reduces the pH-sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…A recent site-directed mutagenesis study showed that SNAT2 inhibition by low pH is largely a consequence of protonation of the extracellular carboxyterminal histidine residue (20). The fall in interstitial fluid pH that occurs even during compensated metabolic acidosis in vivo (43,44) would therefore be expected to inhibit SNAT2 directly.…”
Section: Snat2 Inhibition Mimics the Effects Of Acidosis In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…A recent site-directed mutagenesis study showed that SNAT2 inhibition by low pH is largely a consequence of protonation of the extracellular carboxyterminal histidine residue (20). The fall in interstitial fluid pH that occurs even during compensated metabolic acidosis in vivo (43,44) would therefore be expected to inhibit SNAT2 directly.…”
Section: Snat2 Inhibition Mimics the Effects Of Acidosis In Vivomentioning
confidence: 99%
“…In muscle the molecular identity of the transporter(s) involved has been obscure, but studies in cultured L6 skeletal muscle cells (17,18) have implicated System A neutral amino acid transporters of the SNAT/slc38 transporter family, in particular SNAT2 (19). SNAT2 is also a possible mediator of the effects of acidosis because it is strongly inhibited at low pH (20).…”
mentioning
confidence: 99%
“…In addition, SAT2 is pH sensitive by the same mechanisms as those observed for SN2 as previously mentioned (Baird et al, 2006). Whether these mechanisms are occurring in neurons remains to be determined.…”
Section: Discussionmentioning
confidence: 50%
“…Concerning the SN2 isoform, it is still unknown if post translational mechanisms modulate this transporter but they might undergo similar processes mediated by PKC, since they possess 50% homology (Reimer et al, 2000). Additionally, SN2 activity is regulated by pH, having its activity decreased with lower pH, partially due to an action at the histidine residues found in the transporter (Baird et al, 2006). During HE, it has been described that ammonia leads to intracellular astrocytic alkalinization, as demonstrated in both cell cultures and astrocytes from portacaval-shunted rats (Rose et al, 2005;Swain et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mutation of histidine residues in system A and N amino acid transporters, the Na C -dependent transporters of SLAC38 gene family, produces a reduced transport phenotype (Baird et al 2006). Histidine residue has also been shown to be important in the E. coli Na C / H C exchanger NhaA and Arabidopsis cation/H C exchanger (Wiebe et al 2001, Shigaki et al 2005.…”
Section: Discussionmentioning
confidence: 99%